2007
DOI: 10.1016/s1472-6483(10)60710-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sperm DNA damage, induced acrosome reaction and viability in ICSI patients

Abstract: The DNA damage in human spermatozoa is a relevant predictor of prognosis in male infertility, whereby increased sperm DNA damage impairs the outcomes of artificial reproduction. Theoretically, DNA damage should alter the special cellular functions of human spermatozoa, and lead to diminished acrosome reaction with reduced fertilization rates. Nevertheless, intracytoplasmic sperm injection (ICSI) has been reported to alleviate such negative outcomes due to DNA damage. This study investigated the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 25 publications
2
26
0
2
Order By: Relevance
“…[63] A correlation between progressive motility and normal morphology with acrosome integrity was previously detected in human spermatozoa, also. [64] Another study concerning heavy metal lead with 74 and 100 mg PbCl 2 /kg body weight for four consecutive days indicated impaired motility, the effect of lead toxicity on acrosome integrity, leading to premature reaction, which may finally compromise the ability of spermatozoa to fertilize the oocyte. [59] In an experiment conducted by us concerning mercury, alterations in anterior part of head (acrosome), connection part (connection piece) and in mitochondrial segment of rabbit spermatozoa in vitro were noted at the concentration of 83.3 µg HgCl 2 /mL; [65] where as in the present study similar alterations were observed for cadmium concentrations used, alterations being prominent at the highest concentration.…”
Section: Discussionmentioning
confidence: 99%
“…[63] A correlation between progressive motility and normal morphology with acrosome integrity was previously detected in human spermatozoa, also. [64] Another study concerning heavy metal lead with 74 and 100 mg PbCl 2 /kg body weight for four consecutive days indicated impaired motility, the effect of lead toxicity on acrosome integrity, leading to premature reaction, which may finally compromise the ability of spermatozoa to fertilize the oocyte. [59] In an experiment conducted by us concerning mercury, alterations in anterior part of head (acrosome), connection part (connection piece) and in mitochondrial segment of rabbit spermatozoa in vitro were noted at the concentration of 83.3 µg HgCl 2 /mL; [65] where as in the present study similar alterations were observed for cadmium concentrations used, alterations being prominent at the highest concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that sperm DNA integrity may be altered by environmental exposure to some toxic chemicals [38,39]. DNA fragmentation may be an excellent marker for exposure to potential reproductive toxicants and a diagnostic tool for male infertility [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA integrity is one of the important determinants of normal fertilization and embryo development. A number of studies have investigated the relationship between outcome of assisted reproductive technology (ART) and high DNA damage in sperm (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%